Molecular diversity studies in sweet corn inbred lines using Single Nucleotide Polymorphic markers - Somanatha; Patil, Ayyanagouda; Kuchanur, Prakash; Nair, Sudha; B. Kisan; Yeri, Sharanabasappa B; Vinayan, Madhumal Thayil; Zaidi, Pervez H. (ScienceDomain International, 2025)
Sweet corn (Zea mays L. saccharata) is an important specialty maize, valued for its sweetness and nutritional quality with high consumer demand. The development of superior hybrids relies on genetically diverse inbred lines. Advances in genotyping technologies have transformed the way breeding programs manage their genetic resources. The identification of Single Nucleotide Polymorphisms (SNPs) can improve understanding of the molecular diversity of sweet corn inbred lines and their classification into heterotic groups, which is useful in determining certain crosses to obtain hybrids with higher yield performance. To evaluate molecular diversity, 23 sweet corn inbred lines were genotyped using 97 genome-wide single nucleotide polymorphism (SNP) markers through Kompetitive Allele-Specific PCR (KASP) during 2024-25 at the University of Agricultural Sciences, Raichur, Karnataka. After quality filtering, 56.04% of markers were polymorphic, with polymorphism information content (PIC) values ranging from 0 to 0.375 (mean = 0.39), indicating moderate genetic variability. Cluster analysis using the unweighted pair group method with arithmetic mean (UPGMA) grouped the lines into three major clusters, with most inbreds concentrated in Cluster I, while Clusters II and III contained divergent sweet corn inbred lines (SC-40, SC-9, SC-34 and SC-16), highlighting their potential as valuable sweet corn inbred lines. Principal component analysis (PCA) corroborated the clustering, identifying SC-34, SC-40 and SC-16 as distinct from the core group. The results demonstrate that SNP-based genotyping effectively reveals genetic structure and diversity in sweet corn, further providing a robust framework for heterotic grouping and informed parental selection in hybrid breeding programs.